FRI0185 Sickness Absence during 2003-2012 in Swedish Patients with Spondyloarthritis. (10th June 2014) - Nielsen, C.; Petersson, I.F.; Björk, J.; Englund, M.; Haglund, E.; Jöud, A.
Abstract : Background: Spondyloarthritis (SpA) impacts on several aspects of affected individuals' lives and restricts patients' ability to participate in society, resulting in reduced work productivity and increased sick leave [1]. Thus, SpA imposes financial consequences on the patient as well as the society. However, new pharmacological treatment strategies such as TNF-α inhibitors could have led to a reduction in the amount of sickness absence among SpA patients [2], but so far no study have investigated the effect of the introduction of these treatments in a population setting. Objectives: The aim was to investigate whether the secular trend in the amount of sickness absence in a well-defined cohort of SpA patients differs from that of the general population. Methods: The SpA cohort was identified by searching for relevant ICD-10 codes set by a physician between 1 January 2003 and 31 December 2007 in the Skåne Healthcare Register, covering a population of 1.3 million in southern Sweden. Information on sickness absence (sick leave and disability pension) during the years following diagnosis up until 2012 was obtained from the Swedish Social Insurance Agency. Years when the patient was between 18 and 67 years of age, resident in the Skåne region and alive by December 31st were considered valid for inclusion. A reference cohort consisting of the general population in the same age span with at least one visit to a physician during the year was defined on a yearly basis. The same inclusion criteria as for the SpA cohort were used. The average number of full days of sickness absence per individual and calendar year was calculated for both cohorts. The results of the general population were standardized according to the sex and age distribution of the SpA cohort. Linear regression on the yearly aggregated data was used to test for differences in trends between the cohorts. Results: The SpA cohort contained 38 189 person-years from 7208 patients and the general population contained 7 546 534 person-years from 992 502 individuals. In the SpA cohort, the average number of full days of sickness absence was reduced by 47% between 2003 and 2012, whereas the corresponding reduction in the general population was 36% (Figure). The absolute difference between the cohorts also reduced over time. The yearly reduction in average number of full days of sickness absence was 7.7 in the SpA cohort as compared with 2.3 in the general population ( p <0.001). Conclusions: Between 2003 and 2012, a decrease in the average number of days of sickness absence among SpA patients occurred. The general trend of reduced sickness absence was expected due to policy changes in Sweden. However, the additional reduction occurring in SpA patients may be explained by improved treatment regimens such as the introduction of TNF-α inhibitors. References: Haglund, 2013. PhD thesis 2013:107, Lund University, Sweden. Kristensen et al., 2012. Rheumatol 51: 243-9. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3545